Talking Local: Florida Consumers’ Food Buying Decisions when Given Local Food Information - Joy N. Rumble; Caroline G. Roper (EDIS)
As the fourth of a six-part series about Florida consumers and their perceptions of local food, this EDIS publication focuses on Florida consumers’ purchasing preferences for local food when presented information about where commodities are grown in Florida and the seasonality of Florida-grown products. The Talking Local series focuses on ways Extension agents can assist Florida farmers and ranchers in the labeling, sale, and promotion of locally produced products. It provides Extension faculty who are interested in local food programming or who work with local food clientele with information about Florida consumers’ perceptions of local food. This 5-page publication is a minor revision written by Joy N. Rumble and Caroline G. Roper, and published by the Department of Agricultural Education and Communication, November 2017.